O valor social do trabalho e o dumping social - Franco, Claudia Regina Lovato (2016)
The dissertation researches and reflects upon the business modus operandi and ratio of the garment industry which, with the target purpose of adding value, uses contemporary slavery that spites the human dignity of the employee. It historically contextualizes the social value of work by addressing industrial development and competitive markets, culminating in economic and social imbalance and, social dumping. The study was conducted using an interdisciplinary method drawing on institutes of varying legal fields, economics and sociology, appreciating the macro system of enterprise production. It analyzes the results of labour practices in the justice system by using economic analysis of legal techniques and the precedents of common law, to calculate punitive damages of collective non-material harm to be provided in the Terms for Commitment to Adjustment of Conduct and judicial decisions, modifying entrepreneurial logic to obtain economic advantage by means of precarious labor rights. It demonstrates that there are mechanisms to deter entrepreneurs from engaging in harmful and illegal practices, aspiring them to collectively improve the living conditions of Brazilian workers by providing opportunity for the social value of work. The dissertation aims, through the exercise of effective institutional actions, to break the predatory system of indirect support by the system and the state.